2001
DOI: 10.1128/iai.69.5.2909-2919.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Continuous B-Cell Epitopes on the Protein Moiety of the 58-Kilodalton Cell Wall Mannoprotein ofCandida albicansBelonging to a Family of Immunodominant Fungal Antigens

Abstract: The 58-kiloDalton mannoprotein (mp58) on the surface of Candida albicans is highly immunogenic, is expressed by all C. albicans isolates tested, and elicits strong antibody responses during candidiasis. It belongs to a family of immunodominant fungal antigens with representatives also in different species of Aspergillus. The amino acid sequence of the protein portion of mp58 as deduced from the DNA sequence of its encoding gene (FBP1/PRA1) was used to synthesize a complete set of overlapping dodecapeptides (ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 58 publications
(36 reference statements)
1
37
0
Order By: Relevance
“…Previous studies relating to the epitope mapping of Mycoplasma bovis surface lipoproteins have shown B-cell epitopes to be around three to seven amino acid residues long (22). However, other studies have shown reactive B-cell epitopes relating to fungal, bacterial, or parasitical antigens to be as long as 10 or even 15 residues (15,27,28,29,30), similar to the size of the 10-mer SKQPTIDIDL, ADQTVEEHIG, or QQEVDYIIDH described here.…”
Section: Ididlcdictsupporting
confidence: 66%
“…Previous studies relating to the epitope mapping of Mycoplasma bovis surface lipoproteins have shown B-cell epitopes to be around three to seven amino acid residues long (22). However, other studies have shown reactive B-cell epitopes relating to fungal, bacterial, or parasitical antigens to be as long as 10 or even 15 residues (15,27,28,29,30), similar to the size of the 10-mer SKQPTIDIDL, ADQTVEEHIG, or QQEVDYIIDH described here.…”
Section: Ididlcdictsupporting
confidence: 66%
“…The modulation of confirmed or putative cell surface/membrane/ secreted protein-encoding genes, such as PRA1, DDR48, CSH1, ECM4, HGT12, HGT18, CIP1, INO1, etc., can offer new insight into the molecular mechanisms involved in macrophage phagocytosis and/or Candida escape. One of the most highly upregulated genes identified in the pathogen upon engulfment by the macrophage was PRA1, a gene encoding a cell surface product that has been described as a fibrinogen binding protein (78). In vitro, the PRA1 (pH-regulated antigen 1) gene is activated, along with PHR1 (pH responsive) and its regulator RIM101 (regulator of IME2), when Candida cells are grown at an alkaline pH (15).…”
Section: Resultsmentioning
confidence: 99%
“…Pra1p is a cell wall-associated protein found in both the yeast and hyphal forms of C. albicans: Pra1p becomes highly glycosylated in hyphal-form cells (12) and elicits a strong immune response in infected patients (77). Pra1p was also identified as mp58 (58-kDa mannoprotein) or Fbp1 (fibrinogen binding protein) (45,78). An attractive model for a fibrinogen-binding role of Pra1p would be to link Candida cells to the Mac-1 receptor through fibrinogen (21,22,74), so the expression of this protein during phagocytosis could facilitate Candida adsorption to and escape from macrophages.…”
mentioning
confidence: 99%
“…Another MP of 58 kDa with immunomodulatory activity has been identified in C. albicans. It belongs to a family of fungal immunogenic MPs and stimulates a high production of specific antibodies (Viudes et al 2001). The main mechanism by which the MP produces the modulation of the immune response is related to mannose receptors present on dendritic cells (Mansour et al 2006;Fernández et al 2005).…”
Section: Resultsmentioning
confidence: 99%